Pre-Hispanic and contemporary raw materials use in earthenware production in the Río Mayales subbasin, Chontales, central Nicaragua - Casale, S; Donner, NR; Braekmans, D; Geurds, A (Sidestone Press, 2020)
Since 2007, the Proyecto Arqueológico Centro de Nicaragua (PACEN), directed by Alexander Geurds, has conducted archaeological research in the Río Mayales subbasin, located on the eastern side of Lake Cocibolca in the Chontales province of central Nicaragua. Through the study of procurement strategies of raw materials in the context of archaeological ceramic and lithic industries, the project focuses on understanding pre-Hispanic and contemporary human-environmental relationships in a valley drained by the Río Mayales. This paper provides the results of the first systematic clay-rich soils survey combined with an ethnographic approach to present-day uses of geological resources. Chemical analysis by means of portable X-ray fluorescence (p-XRF) was applied to characterise geologically-based compositional groups throughout the valley. This resulted in an improvement of the limited geological data resolution previously available and the creation of a reference database of p-XRF values for future research in the area that can potentially link ceramic paste composition with clay outcrops. In addition, the ethnographic study generated valuable data regarding contemporary taxonomic soil knowledge in the area, which is transmitted from generation to generation in the context of declining clay-based production strategies, such as pottery manufacture.